The Influence of Use of the Platform Merdeka Mengajar On The Capability of Developing Teaching Tools for Public Primary School Teachers - Cholifah, Puri Selfi; Saputri, Anjani Dian; Putra, Arda Purnama (Proceedings Series of Educational Studies, 2024)
The aim of this research is to determine whether or not there is an influence of the use of the Merdeka Mengajar Platform on the ability to develop teaching tools for teachers in state elementary schools. The type of research is quantitative with regression analysis. The locations used were public elementary schools in Lawang District which had 79 teachers from 9 clusters with a total of 374 teachers. This research uses a cluster random sampling technique. The data collection for this research uses Likert scale numbers. The research results showed that the use of the Merdeka Mengajar Platform was at a moderate level, with the results of a simple linear regression test obtaining a significance of 0.026